Genomic analysis of salmonella species based on 16S rRNA gene sequences - Subramaniam, G.; Puthucheary, S.; Yssin, R.; Pang, T.; Thong, Kwai Lin (Malaysian Society for Molecular Biology and Biotechnology, 2000)
The complete 16S rRNA gene (rDNA) sequences of 15 strains of Salmonella species have been analyzed using direct sequencing of PCR amplicons generated using universal primers. The percentage similarity between the Salmonella spp. studied was very high (96.4 to 99.2) indicating a high degree of sequence conservation within this gene. Among the serovars studied, S. bovismorbificans was found to be the most dissimilar compared to the others. The base substitutions detected occurred throughout the gene with two apparent 'hot-spots' or signature regions, one of which corresponded to the V6 hypervariable region of the 16SrRNA gene. In addition, a 9-base pair insertion and a 5-base pair deletion were discovered in S. waycross and S. matopeni, respectively. We have also detected the presence of putative Salmonella-specific sequences within the 16S rRNA gene which can be used in the design of a species-specific probe. The Salmonella serovars studied appeared to belong to a single species that can be divided into four subclusters. Interestingly, the three human-adapted serovars associated with human enteric fever, that is, S. typhi, S. paratyphi A and S. paratyphi C, were grouped in the same cluster.